Public Relations Strategy Through Social Media in Building a Positive Image in the Era of Society 5.0 At UM Laboratory Middle School, Malang City - Adiyat, Sultana Dimas; Nurabadi, Ahmad; Sunarni, Sunarni; Kusumaningrum, Desi Eri (Proceedings Series of Educational Studies, 2024)
This research aims to describe how public relations strategies through social media can build a positive image of the era society 5.0 at State University of Malang Laboratory Middle School. The approach in this research is through a qualitative approach. The type of research used is a case study. Data collection techniques through in-depth interviews, observation and documentation. The results of this research are (1) the school's perspective on the positive image of schools in the era of society 5.0 through social media at the UM Laboratory Middle School in Malang City, namely (a) following developments, (b) innovation and technology programs, (c) use of social media to build a positive image; (2) a description of the image in the era of society 5.0 at the UM Laboratory Middle School in Malang City through social media, namely the school's social media depicts a situation that is actually true; (3) evaluating the results of the community relations strategy at the first Malang City UM Laboratory Middle School in the short term, the school can see the number of community interactions with the educational content created by the school; (4) the advantages and disadvantages of the social media strategy at UM Laboratory Middle School, Malang City, namely the first advantage of the strategy is that it provides direct , economical information, more reach broad, and innovative educational content. There are 2 shortcomings of the strategy, namely internal and external, from internal is the lack of human resources and time, people's understanding of mistakes that are quickly seen, from external, namely differences in terms and rules that apply to every social media platform the school uses; (5) efforts to support and solution social media strategies at the UM Laboratory Middle School in Malang City. The first is an effort to support the advantages, namely that the school strives for things related to image with sincere and sincere work. Meanwhile, the solution to overcome obstacles is that public relations become a liaison between the school and the community through social media. Keywords: public relations, social media, school image, society 5.0 era